2021
DOI: 10.48550/arxiv.2103.00789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Energy Neutrinos from Choked Gamma-Ray Bursts in AGN Accretion Disks

Jin-Ping Zhu,
Kai Wang,
Bing Zhang
et al.

Abstract: Both long-duration gamma-ray bursts (LGRBs) from core collapse of massive stars and shortduration GRBs (SGRBs) from mergers of binary neutron star (BNS) or neutron star-black hole (NSBH) are expected to occur in the accretion disk of active galactic nuclei (AGNs). We show that GRB jets embedded in the migration traps of AGN disks are promised to be choked by the dense disk material. Efficient shock acceleration of cosmic rays at the reverse shock is expected, and high-energy neutrinos would be produced. We fin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Here we focus on the observational signatures of SN explosions in AGN discs. The highly relativistic electromagnetic signatures of 𝛾-ray bursts (GRBs) and the accretion induced collapse of neutron stars (NS) into BHs have been recently explored (Zhu et al 2020(Zhu et al , 2021aPerna et al 2021b,a). Recently, Zhu et al (2021b) suggested that type Ia supernovae may potentially be observable in AGN discs.…”
Section: Introductionmentioning
confidence: 99%
“…Here we focus on the observational signatures of SN explosions in AGN discs. The highly relativistic electromagnetic signatures of 𝛾-ray bursts (GRBs) and the accretion induced collapse of neutron stars (NS) into BHs have been recently explored (Zhu et al 2020(Zhu et al , 2021aPerna et al 2021b,a). Recently, Zhu et al (2021b) suggested that type Ia supernovae may potentially be observable in AGN discs.…”
Section: Introductionmentioning
confidence: 99%